2018
DOI: 10.1016/j.drugalcdep.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in substance use behaviors and disorders among adult sexual minorities by age, gender, and sexual identity

Abstract: Background: Sexual minorities (SMs) experience elevated rates of substance use behaviors and disorders relative to heterosexuals; minority stress is theorized to contribute to these disparities. As SMs are not a homogenous group, analyses that aggregate SMs across sexual identity, age, or gender obscure important variation among this population. To date, age- and gender-specific disparities have not been rigorously examined using a large national sample. Methods: Using data on 67,354 adults (ages 18–49) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
128
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(133 citation statements)
references
References 43 publications
4
128
1
Order By: Relevance
“…Finally, since three quarters of sexual minority smokers in our sample selfidentified as bisexual, our findings may be more representative of the unique experiences of this sexual minority subgroup. Tobacco use disparities may vary by distinct sexual minority identities (e.g., gay, lesbian) or different gender identities (e.g., transgender) (Callis, 2013; Hoffman et al, 2018; Schuler et al, 2018). Further research is warranted to better understand smoking antecedents among distinct sexual and gender identities.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, since three quarters of sexual minority smokers in our sample selfidentified as bisexual, our findings may be more representative of the unique experiences of this sexual minority subgroup. Tobacco use disparities may vary by distinct sexual minority identities (e.g., gay, lesbian) or different gender identities (e.g., transgender) (Callis, 2013; Hoffman et al, 2018; Schuler et al, 2018). Further research is warranted to better understand smoking antecedents among distinct sexual and gender identities.…”
Section: Discussionmentioning
confidence: 99%
“…SM‐related discrimination has been found to be associated with increased tobacco, alcohol and drug use in SM populations , although differentially associated with substance use across SM identities . We found that while SM‐related discrimination was significantly higher among SM, discrimination was not significantly associated with SUD among SM‐identifying individuals.…”
Section: Discussionmentioning
confidence: 49%
“…Effective strategies to incorporate social support may require assessing the functional support received and tailoring interventions based on social networks. SM-related discrimination has been found to be associated with increased tobacco, alcohol and drug use in SM populations [13,17,62,63], although differentially associated with substance use across SM identities [8,13,64]. We found that while SM-related discrimination was significantly higher among SM, discrimination was not significantly associated with SUD among SM-identifying individuals.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations